CLINICAL AND LABORATORY CHARACTERISTICS OF POST-COVID SYNDROME IN CHILDREN AGED 5–12 YEARS IN RELATION TO IGG LEVELS TO SARS-COV-2 - Liamtseva, Olena (Eastern Ukrainian Medical Journal, 2025)
Coronavirus infection caused by SARS-CoV-2 is a risk factor for the development of post-Covid syndrome in pediatric patients. The clinical presentation of pediatric post-COVID syndrome is highly heterogeneous. The identified associations between clinical, inflammatory, and coagulation parameters highlight potential mechanisms underlying prolonged post-COVID manifestations and may contribute to the development of improved monitoring strategies in pediatric practice. Aim of the study. To investigate the clinical and laboratory characteristics of post-COVID syndrome in children aged 5–12 years, with a focus on inflammatory, immune, and coagulation markers, and to determine the correlations between clinical manifestations and laboratory parameters. Materials and methods. A prospective open cohort study was conducted involving 110 children aged 5–12 years, including 80 patients with post-COVID syndrome and 30 children without a history of SARS-CoV-2 infection (control group). Clinical symptoms, complete blood count, coagulation profile, levels of IgG to SARS-CoV-2, C-reactive protein (CRP), fibrinogen, and electrocardiographic findings were assessed. Statistical analysis included calculation of means, standard deviations, medians, 95% confidence intervals, and Pearson or Spearman correlation coefficients. Statistical significance was set at p < 0.05. Results. Most children with post-COVID syndrome exhibited asthenic, neurological, respiratory, and gastrointestinal manifestations: fatigue (91.3%), fever (96.3%), headache (57.5%), sleep disturbances (72.5%), and attention deficit (63.8%). The mean hemoglobin level was 130.4 ± 14.9 g/L, erythrocyte sedimentation rate (ESR) – 18.6 ± 12.4 mm/h, and fibrinogen – 3.86 ± 1.14 g/L. Elevated CRP (>10 mg/L) was observed in more than half of the patients, indicating persistent low-grade inflammation. A significant positive correlation was found between fibrinogen and IgG to SARS-CoV-2 (r = 0.27; p = 0.017), confirming the association between humoral immune activation and ongoing inflammatory response. Coagulation parameters demonstrated a tendency toward hypercoagulability, while ECG findings revealed predominantly functional changes, such as sinus arrhythmia (28.8%) and incomplete right bundle branch block (23.8%). Conclusions. Post-COVID syndrome in children is a multisystem condition characterized by sustained inflammation, activation of the coagulation cascade, and endothelial dysfunction. Identified clinical and laboratory correlations highlight the contribution of immunoinflammatory mechanisms in the development of post-COVID alterations and emphasize the need for dynamic monitoring and long-term follow-up of affected children.